2021
DOI: 10.1039/d1sc00295c
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-bio catalysis using carbon supports: application in H2-driven cofactor recycling

Abstract: Heterogeneous biocatalytic hydrogenation is an attractive strategy for clean, enantioselective C=X reduction. This approach relies on enzymes powered by H2-driven NADH recycling. Commercially available carbon-supported metal (metal/C) catalysts are investigated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…These inorganic functionalized electrodes are in big competition with enzymatic systems where electrodes surfaces are modified with electrocatalytic enzymes (e.g., NAD + reductase for NADH regeneration, ferredoxin NADP + reductase for NADPH regeneration), and hydrogenase for hydrogen production and oxidation . The choice between inorganic and enzymatic systems depends on the activity, stability, and economic viability of the process in which the catalyst is applied.…”
Section: Recent Examples About the Application Of Electroanalytical T...mentioning
confidence: 99%
“…These inorganic functionalized electrodes are in big competition with enzymatic systems where electrodes surfaces are modified with electrocatalytic enzymes (e.g., NAD + reductase for NADH regeneration, ferredoxin NADP + reductase for NADPH regeneration), and hydrogenase for hydrogen production and oxidation . The choice between inorganic and enzymatic systems depends on the activity, stability, and economic viability of the process in which the catalyst is applied.…”
Section: Recent Examples About the Application Of Electroanalytical T...mentioning
confidence: 99%
“…The most popular enzyme systems right now are glucose-dehydrogenase (Sorgedrager et al, 2008;Liang et al, 2010b;Huisman et al, 2010;Gong et al, 2017;Chen et al, 2021) and formate dehydrogenase (Shaked and Whitesides, 1980;Seelbach et al, 1996;Gröger et al, 2004;Jiang et al, 2020). Very recently, Vincent and coworkers reported significant advances in the use of hydrogenases (Reeve et al, 2012;Reeve et al, 2017;Zor et al, 2017;Zhao et al, 2021) enabling H 2 as cosubstrates.…”
Section: Regeneration Of Reduced Nicotinamide Cofactorsmentioning
confidence: 99%
“…Vincent and co-authors reported the chem-bio catalyzed H 2 -driven NADH regeneration with reductase governing NAD + reduction. [6] In addition to enzymes, organometallic complexes and metal nanoparticles (NPs) are the most widely used hydrogenation catalysts. [7] However, they confront big challenges in H 2 -driven NAD(P) + reduction.…”
Section: Introductionmentioning
confidence: 99%